Pengendalian Kualitas Dengan Pendekatan SPC Dan FMEA Pada Proses Perakitan Smartphone (Studi Kasus : PT. Adi Reka Mandiri): (Studi Kasus : PT. Adi Reka Mandiri) - Andika Lesmana; Pratiwi, Irnanda; MZ, Hermanto (Nusantara of Engineering (NOE), 2023)
PT. Adi Reka Mandiri (ARM) is one of the Local Electronic ManufacturingServices that produces finished goods such as STB (Set Top Boxes), NetworkRouters and Smartphones. One of the products is Smartphone products, there arestill many defective products that are not in accordance with company standards.The percentage of smartphone product defects in the period January 2022 - June2022 reached 0.57%, exceeding the tolerance for product defects in the company,which was 0.1%. The types of smartphone product defects include LCD Crack, LCDBlack Spot, Speaker No Sound, Battery Leaking, Camera Fail, and FingerprintFail. This study aims to analyze the causes of defects and provide recommendationsfor improvements to improve quality. The method used is SPC (StatisticalProcessing Control) and FMEA (Failure Mode and Effect Analysis). The stages inthe research began with collecting data, analyzing data with SPC, determining RPNvalues using FMEA, and recommending improvements. The results of the researchshow that the most dominant product defects are LCD Black Spot (47%), LCDCrack (22%), and Camera Fail (15%), the three defects account for 84%. The causeof disability is caused by human, material, and machine factors. The highest RPNvalue is 432 on a cracked LCD due to a lack of machine settings. The improvementrecommendation is to perform each configuration before assembling a new type.